Pancreatic Adenocarcinoma in a Cat - Matte Weiss, Janaina; Ganzer Mezzomo, Daniele; Genro Cony, Fernanda; Jung, Jenifer; Sonne, Luciana; Driemeier, David; Vieira Amorim da Costa, Fernanda (Acta Scientiae Veterinariae, 2023)
Background: Despite being rare in domestic animals, pancreatic adenocarcinoma is the most common malignant tumor of the feline pancreas. Due non-specificity of clinical signs in cats and the late diagnosis of the neoplasm, it is necessary tounderstand this disease better, to contribute for the knowledge of its early recognition and treatment. Thus, this study aims to report a case of metastatic pancreatic ductal adenocarcinoma in a cat, focusing on the main clinical aspects, diagnosis, and prognosis of this disease, in addition to the description of the presentation of peritoneal carcinomatosis. Case: A 14-year-old male neutered mixed breed cat, was referred to the Feline Medicine Service (MedFel) of the Hospital de Clínicas Veterinárias (HCV) - Universidade Federal do Rio Grande do Sul (UFRGS), Porto Alegre, RS, with a history of hyporexia, constipation and increased abdominal volume for 3 days, besides mild difficulty in locomotion and progressive weight loss in the last 6 months. On the physical examination, the patient was alert, with a body condition score of 6/9; muscle condition score 1/4 and moderate dehydration of 7%. Popliteal lymph nodes were enlarged, and abdominal distension was evident. Around 200 mL of a slightly cloudy, straw-yellow liquid were drained from the abdominal cavity. After draining the fluid, a new abdominal palpation was performed, and there were fecal retention and a palpable mass in the right hypogastric region. The result of the cytological analysis of the fluid was consistent with a protein-rich transudate, suggesting neoplastic effusion of epithelial origin. Hematological and biochemical changes included leukocytosis due to neutrophilia, monocytosis, lymphopenia, thrombocytosis and azotemia. On abdominal ultrasound, the patient had free fluid in the abdominal cavity, and the gallbladder had discreet of biliary sludge. The intestines showed some corrugated segments with other segments lacking definition of its layers, and without peristaltic movements, suggesting intestinal neoplasia. Pancreas and adrenals were not visualized. On the chest X-ray, moderate opacification of lung fields with a diffuse interstitial pattern was observed, suggesting lung metastasis. The patient presented an acute worsening of the clinical condition and the owner requested euthanasia. The patient was referred for necropsy and based on the macroscopic and microscopic changes, the post-mortem diagnosis was metastatic pancreatic ductal adenocarcinoma with peritoneal carcinomatosis. Discussion: The clinical presentation of cats with exocrine pancreatic neoplasia is nonspecific, as clinical signs are common to several diseases, such as anorexia, vomiting, abdominal pain, weight loss with normal appetite, jaundice, depression, and lethargy. Complementary blood tests also do not provide data that could lead to the suspicion of pancreatic neoplastic disease. In the present case, the diagnosis of metastatic pancreatic ductal adenocarcinoma with peritoneal carcinomatosis was only possible post mortem. The pancreas is a difficult organ to assess adequately using most diagnostic imaging methods, so histopathology is still the method of choice for differentiating pancreatic tissue comorbidities. Therefore, exploratory laparotomy should be instituted to provide tissue samples from the pancreas and its metastases for histopathological diagnosis, whenever ultrasound or other imaging methods indicate suspicious abdominal changes. The literature reports that less than 10% of affected cats treated with complete surgical removal of the mass and chemotherapy alone will survive more than a year, and the average time for untreated cats is only 6 days. The prognosis of this disease is bad and most cats are euthanized, due to rapid clinical worsening. Therefore, diagnosis is essential to determine an adequate prognosis in advanced cases and to support therapeutic decisions or euthanasia. Keywords: pancreatic neoplasia, abdominal carcinomatosis, ductal adenocarcinoma, feline. Título: Adenocarcinoma pancreático em um gato Descritores: neoplasia pancreática, carcinomatose abdominal, adenocarcinoma ductal, felino.